Distributed Video Coding Using Turbo Codes and Second Generation Wavelets - Ponchet, A.; Iano, Y. (Revista IEEE América Latina, 2008)
Distributed video coding is a new paradigm for video compression in opposition over the existing video coding standards like MPEG-x and H.26x families. These codecs make use of motion estimation algorithms, the main part of the compression process of the video signal. Hence, the compression process demands a high computational cost and high performance of the encoder. The present work proposes a video compression scheme based on the lossy distributed source coding theory. The proposed compressor encodes the odd frames and the even frames separately using turbo codes and the discrete wavelet transform. The decoding process is performed in a iterative manner and explores the statistical dependency of the video frames of the original sequence. This approach gives a great encoding runtime reduction and allows the implementation at devices with limited computation power and memory. Simulation results show the good performance of the proposed codec in comparison with the state of the art video compression standard H.264/AVC.